2019
DOI: 10.1371/journal.pone.0217155
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-tocopherol in intravenous lipid emulsions imparts hepatic protection in a murine model of hepatosteatosis induced by the enteral administration of a parenteral nutrition solution

Abstract: Intestinal failure-associated liver disease (IFALD) is a risk of parenteral nutrition (PN)-dependence. Intravenous soybean oil-based parenteral fat can exacerbate the risk of IFALD while intravenous fish oil can minimize its progression, yet the mechanisms by which soybean oil harms and fish oil protects the liver are uncertain. Properties that differentiate soybean and fish oils include α-tocopherol and phytosterol content. Soybean oil is rich in phytosterols and contains little α-tocopherol. Fish oil contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Our results showed statistically significant improvements in GGT and ALT 1.5 years after transitioning to SMOFlipid, supporting previously published literature showing minimal hepatic effects or development of IFALD following transition to SMOFlipid 5,13,19‐21 . Prior studies have demonstrated conflicting data on SMOFlipid effects on hepatic enzyme trends.…”
Section: Discussionsupporting
confidence: 87%
“…Our results showed statistically significant improvements in GGT and ALT 1.5 years after transitioning to SMOFlipid, supporting previously published literature showing minimal hepatic effects or development of IFALD following transition to SMOFlipid 5,13,19‐21 . Prior studies have demonstrated conflicting data on SMOFlipid effects on hepatic enzyme trends.…”
Section: Discussionsupporting
confidence: 87%
“…In adult mouse models, mice that are enterally fed PN solution containing amino acids and glucose while being administered SO-LE intravenously rapidly develop hepatic steatosis [ 69 , 70 , 71 , 72 , 73 ]. The administration of FO-LE does not lead to steatosis in this model [ 71 , 73 ].…”
Section: Lipid Emulsion Composition and Clinical Effectsmentioning
confidence: 99%
“…Fell et at. administered vitamin E supplemented SO-LE enterally to adult mice which prevented steatosis and maintained healthy hepatic architecture compared to regular SO-LE [ 70 ]. In a similar study, enteral administration of FO-LE was supplemented with vitamin E for 19 days [ 30 ].…”
Section: Lipid Emulsion Components That Modify Pnac Incidencementioning
confidence: 99%
“…At present, the fat emulsions used in clinical practice are mostly based on soybean oil. Soybean oil-based fat emulsions are rich in long-chain fat emulsions, which can affect granulocyte activity under severe stress such as trauma and infection, resulting in impaired immune function and increased lipid peroxidation, which in turn increases organ function damage [ 10 , 11 ]. This tendency to increase the inflammatory response often makes the use of soybean oil-based fat emulsions in a dilemma clinically.…”
Section: Introductionmentioning
confidence: 99%